2016
DOI: 10.7150/ijbs.16060
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Doxycycline with Phytochemicals and Micronutrients Against Active and Persistent Forms of Borrelia sp

Abstract: Phytochemicals and micronutrients represent a growing theme in antimicrobial defense; however, little is known about their anti-borreliae effects of reciprocal cooperation with antibiotics. A better understanding of this aspect could advance our knowledge and help improve the efficacy of current approaches towards Borrelia sp. In this study, phytochemicals and micronutrients such as baicalein, luteolin, 10-HAD, iodine, rosmarinic acid, and monolaurin, as well as, vitamins D3 and C were tested in a combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Similarly, Goc et al, 2016, showed that Doxycycline is synergistic in vitro with certain phytochemicals and micronutrients, including Vitamin C, in the in vitro killing of the vegetative spirochete form of Borrelia spp., the causative agent underlying Lyme disease [ 38 ]. Vitamin C has also been shown to be synergistic with Tetracycline and Chloramphenicol, against the pathogenic bacteria, Pseudomonas aeruginosa [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Goc et al, 2016, showed that Doxycycline is synergistic in vitro with certain phytochemicals and micronutrients, including Vitamin C, in the in vitro killing of the vegetative spirochete form of Borrelia spp., the causative agent underlying Lyme disease [ 38 ]. Vitamin C has also been shown to be synergistic with Tetracycline and Chloramphenicol, against the pathogenic bacteria, Pseudomonas aeruginosa [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their anti-inflammatory and cell protective properties were also intensively researched worldwide (Woo et al 2006;Cheng et al 2007;Hsieh et al 2007;Nabavi et al 2015). It is worth noting that their cooperation with antibiotics is remarkable as shown by ours and many other research groups Su et al 2014;Qian et al 2015;Siriwong et al 2015;Cai et al 2016;Goc et al 2016). According to the aforementioned data, baicalein and luteolin have a broad spectrum of antimicrobial activity, but their efficacy is shown to be in relatively high effective concentrations.…”
Section: Discussionmentioning
confidence: 68%
“…; Goc et al . ). According to the aforementioned data, baicalein and luteolin have a broad spectrum of antimicrobial activity, but their efficacy is shown to be in relatively high effective concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…For example, grape (Vitis vinifera) seed extract [8], sugar leaf (Stevia rebaudiana) [9] and cat's claw (Uncaria tomentosa) [6] have shown potential activity against acute Borrelia spirochetes and the nongrowing stationary phase. This is further supported by the use of treatments where phytochemicals are used in combination with antibiotics [10] or micronutrients such as vitamin D [11], enabling lower LD 50 (median lethal dose) and MIC (minimum inhibitory concentration) concentrations against latent rounded forms of B. burgdorferi. This demonstrates a wide future potential of novel bioactives as both individual and synergic compounds for possible anti-Borrelia treatments [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by the use of treatments where phytochemicals are used in combination with antibiotics [10] or micronutrients such as vitamin D [11], enabling lower LD 50 (median lethal dose) and MIC (minimum inhibitory concentration) concentrations against latent rounded forms of B. burgdorferi. This demonstrates a wide future potential of novel bioactives as both individual and synergic compounds for possible anti-Borrelia treatments [10,11].…”
Section: Introductionmentioning
confidence: 99%